基于正交试验和有限元分析的谐波传动柔轮杯体结构优化 - 董惠敏; 李德举; 齐书学 (Jixie chuandong)
The flexspline,as a critical component of harmonic drive,of which the fatigue strength directly affects the bearing capacity and service life of harmonic drive.Establishes the parameterized model of flexspline contact analysis based on the APDL is established.Considering the gap of bearing and the assembly clearance of the flexspline and wave generator,the stress field of the flexspline is obtained using finite element method.On this basis,orthogonal test is applied to study the impact of the structural parameters on the maximum stress of flexspline cup.Further,an optimization model is built to minimize the maximal stress.Finally,the optimal parameters of flexspline cup are obtained using zero-order method.